INTESTINAL MICROFLORA IN CHILDREN WITH INFANTILE COLIC - Levenets, S.S.; Horobets, N.M.; Kirzhner, G.D.; Sabadash, V.Ye. (World of Medicine and Biology, 2021)
Functional gastrointestinal disorders are the most prevalent pathological conditions in children. Infantile colic is the most common problem during the first months of life. One of the possible mechanisms that could be pathogenically involved in the occurrence of the infantile colic is changes in intestinal microbiota. This research aims to study the gut microbiota in children with infantile colic. We examined gut microflora of 57 children (aged from 1 to 5 month) with intestinal colic. It was found that children with infantile colic have gut microbiome disorder that is manifested in decreased numbers of obligate anaerobes, increased growth of facultative anaerobes of the Proteobacteria phylum, mainly species of the Enterobacteriaceae family, increased number of microorganisms of the Firmicutes phylum, especially of the Staphylococcaceae family, and increased numbers of Candida species. An increased number of gram-negative (K. pneumonia) and gram-positive (S. aureus) opportunistic microorganisms characterized gut microbiome in children with infantile colic. Candida species and S.aureus were the most common pathogens to colonize the gut. Among the frequently seen microbial communities, three- and two-component ones prevailed. Most commonly Candida species formed communities with Staphylococcus aureus, Klebsiella pneumoniae, and Enterococcus faecalis. Indirect evidence of gut redox potential shift to the acid side in children with infantile colic are the emergence of opportunistic flora that is usually cultivated in neutral or acidic environments (Candida species, EHEC) and reduction of the numbers of microflora representatives that produces organic acids (commensal E.coli, Lacto- and Bifidumflora).